2013
DOI: 10.3802/jgo.2013.24.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Histologic distribution of borderline ovarian tumors worldwide: a systematic review

Abstract: ObjectiveThe histologic types of borderline ovarian tumors (BOTs) exhibit striking differences in clinical behavior and prognosis. Yet, there is no information available on the histologic distribution of BOTs according to geographic region. The purpose of this study was to systematically review this issue worldwide.MethodsA comprehensive search of the literature was conducted using electronic databases. Studies were eligible if BOTs were investigated and the histologic distribution of the data was shown. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 51 publications
2
24
0
2
Order By: Relevance
“…Asian women have a high incidence of BOTs, with varying histopathologic subtypes, especially mucinous BOTs [25] . The authors found that all 5 parameters showed better accuracy for BOTs that were classified as non-cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Asian women have a high incidence of BOTs, with varying histopathologic subtypes, especially mucinous BOTs [25] . The authors found that all 5 parameters showed better accuracy for BOTs that were classified as non-cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the USA [31], France [32] and Italy [33] have reported serous-type BOTs as the most common (60-74%), while studies in Korea [34] and Japan [35] have reported mucinous-type BOTs as the most common (68-76%). According to a recent systematic review, in general, serous-type BOTs were the predominately identified histology in North America, the Middle East, and Europe, while mucinous-type BOTs predominated in East Asia [36]. …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the incidence of M-BOT is reported to be higher in nonwhite patients comparable to invasive ovarian cancer. 10 Serous BOTs are confined to 1 ovary in 75% of cases. Extraovarian distribution is more frequent in S-BOT (25%) represented by peritoneal implants (21.7% any implants, 3.6% invasive implants).…”
Section: Pathologymentioning
confidence: 99%